Commentary: Observations on the Study of Legal Education—Circa 1980 - Thomas B. Curtis (Washington University Law Quarterly, 1981)
I have reached a number of controversial assumptions about the practice, the teaching, and the study of law in the mid-twentieth century America. While each assumption should be fully supported by facts and fair arguments, a commentary of short length on a subject this broad will not so permit. Consequently, what follows will be more of an outline than a discussion in depth on any one of the topics.
Keywords: Law schools; Legal education; United States